Ambient temperature dependent changes in DNA methylation in Arabidopsis thaliana Col-0 and the decrease in DNA methylation 1 mutant - Suze Blom; Harm Nijveen; Froukje van der Wal; Christina Papastolopoulou; Sara Diaz Trivino; Gerco C. Angenent; Richard G.H. Immink (Plant Stress)
Dynamic DNA methylation is involved in the acclimation of plants to the environment. However, the exact role of DNA methylation in acclimation to ambient temperature is unresolved. We aimed to explore the potential role of DNA methylation in the ambient-temperature response in Arabidopsis thaliana with a specific focus on the flowering time response. Here, we show that the hypomethylation mutant decrease in DNA methylation 1 (ddm1) is hypersensitive in its ambient temperature-dependent flowering response. We found significant effects on transcription of transposable elements (TEs) in ddm1 after a 24-hour switch from 16 °C to 25 °C, whereas this switch did not lead to this activation in Col-0. To explore the role of DNA methylation after this temperature switch, we analysed both differentially methylated regions (DMRs) and differentially methylated cytosines (DMCs). Both DMRs and DMCs were more prevalent in ddm1 than Col-0, and more prevalent in TEs compared to other genomic features. Especially the number of DMCs in ddm1 was drastically increased compared to Col-0 (47,854 versus 318, respectively). Our results with the hypomethylated ddm1 mutant indicate that DDM1 prevents DMC accumulation after a change in ambient temperature. Based on these findings, we propose the threatened methylome hypothesis, which states that DDM1 helps to buffer against overaccumulation of changes in DNA methylation and consequent TE activation. This safeguards genome stability and prevents hypersensitivity to ambient temperature in the flowering time response.